'Doing fence-sitting': a discursive analysis of clinical psychologists' constructions of mental health and its impact on service-users - Lofgren, Axel (2013)
Introduction: The notion of mental health has been used to designate a range of concepts and a great deal of controversy surrounds discussions about the meaning of the construct. Despite its elusive nature, there is a growing body of research indicating that the ways in which healthcare professionals conceptualise mental health may have important clinical implications. It is argued that the quantitative methodologies employed by previous studies have not been able to capture the complexity of healthcare professionals’ accounts.